A história de Santarém sob a ótica de Arthur Reis - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2024)
Arthur César Ferreira Reis is an emblematic figure for the intellectual scenario of the Amazon in the 20th century, given his vast experience as a politician and researcher on Amazonian issues. However, his trajectory is little remembered by historiography. Based on this assumption, the research aims to analyze the work "Santarém: its historical development" with the general objective of understanding the representations constructed by the historian about the city of Santarém and, more specifically, filling a gap in studies on Kings and Santarém historiography. Therefore, the theoretical basis was based on research by Sousa (2009) and Dantas (2014) who analyze the characteristics of Arthur Reis's historical writing. Methodologically, to understand the perspective bequeathed to Santarém by Reis, Chartier's (1990) notion of "representation" was used, this being the main point of analysis for the work. From the analysis it was found that Arthur Reis has a Lusophile and developmentalist historical writing, which is the basis for his vision of Santarém. Thus, despite naming it "capital of Lower Amazonas", the historian presents us with a chronicle without much critical analysis where his focus is to describe a laudatory history of an Amazonian community that, however, has a lot to modernize.
Keywords: Historiografia; Arthur Reis; Amazônia; Santarém; CNPQ:: CIÊNCIAS HUMANAS